Uso dos resíduos da construção civil para a produção de pavimento intertravado a base de concreto de cimento portland e escória - Edmundo Abi-ackel (2009)
Construction and demolition are two steps where the generation of waste is imperative, given the low industrialized processes. Due to the growth of cities, the demand for raw materials is becoming more expressive and their deposits more distant from consumer centers. Consequently there is an increase in the generation of rubble and storage areas. The granulated slag of blast furnace in Brazil, mainly in the southeast, has had little exploitation, given the economic model, also requiring large storage yards. This dissertation discusses the possibility of these of granular slag from blast furnace activated with sodium hydroxide and construction and demolition wastes as an alternative to reduce consumption of Portland cement and aggregates to manufacture pre-fabricated pieces of concrete for interlocking paving. The use of concrete-based waste and slag is an alternative on paving, one of the pillars of the country's infrastructure. Alternative technologies become important to contribute to the reduction of energy consumption of production processes and reducing the costs of public urban streets. The characteristics of studied concretes are discussed, with emphasis on the absorption and the elasticity modulus.